PENGEMBANGAN E-JOBSHEET UNTUK MENINGKATKAN KEMAMPUAN MEMBUAT JURNAL DAN LAPORAN PADA PRAKTIKUM PENGHANTAR PANAS - Fegi Oktapiani, - (2021)
Vocational High School (SMK) is education at the secondary level that prepares students to enter the world of work armed with knowledge and expertise. Supporting aspects to improve knowledge and expertise on psychomotor and cognitive assessments, namely the need for learning media for journal making and practicum reports. This research is a development research from relevant previous studies, where the researcher developed a practicum e-jobsheet as a learning medium with heat-conducting material in the basic subject of Agricultural Product Processing. This development research aims to 1) determine the feasibility of the developed e-jobsheet media, 2) determine the ability of students in making journals and practical reports, 3) determine the abilities of students' skills when practicing using e-jobsheets. The method used is ADDIE consisting of five stages, namely analyze, design, development, implementation and evaluation plus media testing to determine the cognitive and psychomotor results of students. Feasibility assessment by media experts, material experts and linguists, the e-jobsheet media is very suitable for use as a learning medium. The results of the assessment of students' abilities in making journals and practicum reports using the "very good" e-jobsheet. The results of students' skills skills when practicum using e-jobsheets are "very good" Keywords: e-jobsheet, practicum journal, cognitive, instructional media, psychomotor